Regulating polysaccharide structure and bioactivity via free radical degradation: a review of mechanisms, effects, and application prospects - Li, Jieming; Lv, Shuaiyi; Hu, Yulong; Kong, Yuanfang; Cai, Juntao; Nan, Guanglei; Jiang, Shiqing; Yang, Shaohua; Dong, Chunhong (Frontiers in Nutrition, 2026)
Natural polysaccharides from food sources (e.g., ginseng, seaweed, apricot, larch) have diverse bioactivities (antioxidant, immunomodulatory, hypoglycemic) that are closely related to human nutritional health, but their structural heterogeneity (e.g., molecular weight, monosaccharide composition) impedes clear structure-activity relationship (SAR) establishment. Free radical degradation, a mild method preserving labile groups (e.g., sulfate esters), is an effective solution. This review summarizes its role in regulating polysaccharide SAR: focusing on hydroxyl radical (⋅OH)-mediated mechanisms (via Fenton-like reactions: processes that generate hydroxyl radicals through the reaction of H2O2 with metal ions/ascorbic acid), a three-stage kinetic model (rapid depolymerization, main chain scission, slow degradation), and site-specific modifications. Key structural changes (molecular weight reduction, functional group exposure/transformation, monosaccharide composition alteration, conformational shifts) are analyzed, and their synergistic enhancement of bioactivities (antioxidant, immunomodulatory, etc.) is elaborated. Such as, reduced molecular weight improves solubility, while exposed sulfate groups strengthen target binding. The optimal molecular weight range (10–1,000 kDa) and its dependence on polysaccharide sources/activity types are identified. Current challenges (degradation controllability, product characterization) and future directions (advanced techniques like High Performance Liquid Chromatography-Mass Spectrometry (HPLC-MS), Nuclear magnetic resonance (NMR), smart degradation systems) are discussed. This review provides guidance for precise preparation of functional polysaccharides.